(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The characterization of edible tissues of fishes consumed by humans is very important for determination of several toxic and potentially toxic elements, ensuring the food safety. The Instrumental Neutron Activation Analysis (INAA) comparative method allows the determination of several of these elements, as well as others, for example of nutritional character. This study is part of an International Atomic Energy Agency (IAEA) technical cooperation project of Latin America and Caribbean countries to ensure the quality of food and biomonitoring of contaminants in shellfish and fishes. Ten specimens of 4 of the most consumed fish in São Paulo city: whitemouth croaker (Micropogonias Furnieri), smooth weakfish (Cynoscion learchus), common snook (Centropomus undecimalis) and Brazilian sardine (Sardinella brasiliensis) were analyzed. Complete procedures for analysis, which includes purchase in the largest warehouse in Latin America, transport to the laboratory, storage, freeze-drying, milling, weighting and others preparations of the subsamples, and the short irradiation parameters for the determination of Br, Cl, K, Mg, Mn and Na are reported. Results obtained under the same irradiation conditions for reference materials (oyster and mussel tissues) for macro and microelements are presented and are in agreement with their certificates, which indicate that the performed analyses were appropriate. Regarding to the mass fraction values obtained for the fish samples, they were in agreement with the literature.